Digital Marketing in Facing Business Competition in the Digital Era: A Conceptual Study as a Reference for Researchers - Bimaruci Hazrati Havidz, Hazimi (International Journal of Advanced Multidisciplinary, 2024)
The development of digital technology has significantly transformed the business competition landscape, compelling companies to adapt to more innovative and efficient strategies. Digital marketing has emerged as an effective approach to address these challenges, allowing companies to expand their market reach, enhance consumer interaction, and measure marketing performance in real-time. The application of digital marketing strategies has become an effective solution in achieving these goals. This research examines how digital marketing can be utilized to strengthen consumer trust, build a strong corporate image, and increase customer loyalty. The study consists of several sections. First, a literature review focuses on digital marketing. Second, the research model and propositions developed in this study are based on a literature review of previous research, and the relationship between digital marketing, trust, corporate image, and customer loyalty is discussed in-depth. The results of the study show that an integrated digital marketing strategy not only helps companies survive in the competition but also builds long-term relationships with customers, ultimately enhancing trust and strengthening the corporate image in the market. The proper implementation of this strategy is a key factor in business success in the digital era.